Instalasi Energi Surya Pada Alat Desalinasi Air Untuk Masyarakat Di Perbatasan - Rachmat Setiawibawa; Dekki Widiatmoko; Rafi Maulana Al-farizi; Eriski Prawira (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Solar energy installations mathematically and visualization using the Solar Global Atlas Software simulation. The data obtained is that the highest energy occurred in the second test with the result of 365.7 Wh with the maximum power generated by solar panels of 93.28 W, battery charging energy of 321.5 Wh with a maximum battery charging power of 76.78 W. Sunhour that occurs is obtained 3.66 h with solar panel efficiency that occurs at 12.8%. The research methods used include quantitative research methods by taking data using measuring instruments using literature studies, simulations and experiments to then be processed using related formulas in the implementation of the research.